Lo cotidiano: una forma básica de mirar la diversidad - Dora María Hernández-Vargas (Revista Electrónica Educare)
By using a fragment of Jorge de Bravo’s poem, the author of this essay takes the reader into a journey of thinking about the significance of how respect for human diversity must be approached on a daily basis, since a regular need for tenderness, supper, silence, bread and home.